"THE INFLUENCE OF COMPANY FUNDAMENTAL INTERNAL FACTORS ON STOCK RETURN IN THE COAL MINING SECTOR ON THE INDONESIA STOCK EXCHANGE" (Case Study of BUMN PT Bukit Asam Tbk) - Selfy Maulidya; M. Sobarsyah; Andi Ratna Sari Dewi (Scientium Management Review, 2023)
This study intends to examine how fundamental factors affect coal mining company share prices. Investment through the capital market is one way to increase wealth and encourage economic growth in Indonesia. Fundamental analysis is used as the basis for selecting stocks with the expected intrinsic value. Some of the fundamental factors considered in this study to obtain the expected stock return are financial ratios such as Earning Per Share, Price to Earning Ratio, and Return On Equity. The data in this study are historical data on the share prices of state-owned companies in the coal mining sector, and financial reports. Multiple linear regression analysis is the analytical technique used to examine the impact of underlying factors on stock prices. The results of this study indicate that several fundamental factors of Return On Equity have a significant influence on the stock prices of coal mining companies. However, variables such as the Price Earning Ratio do not have a significant effect on stock prices. This shows that investors tend to pay more attention to the company's profit and earnings per share factors in choosing stocks for investment. This research contributes to the understanding of the influence of fundamental factors on the stock price of coal mining companies. The results can be a reference for investors in choosing stocks that have higher profit potential. However, this study also has limitations such as the limited number of companies studied and the limited research time period. Future research could involve more companies and look at the impact of fundamental factors over a longer period of time.